Transecções medulares altas inibem a motilidade gastrintestinal em ratos acordados - Gondim, Francisco de Assis Aquino (1999)
Spinal cord injury leads to marked changes of the digestive functions. However, there is a limited amount of studies addressing the changes on the motility of the upper gastrointestinal tract. The present study demonstrates the effects of spinal cord transections (SCTs), either cervical (between the seventh cervical and first thoracic vertebrae) or thoracic (between the fourth and fifth thoracic vertebrae) lesions on the gastric emptying (GE), intestinal transit (IT) and gastrointestinal fa-ansit (GIT) of liquid in awake Wistar rats. The study is divided into three main sections, which represents the evolution of our investigations on the referred subject. In the first section (protocol l, N = 65, 180-220 g) we observed that the GE, IT and GIT are inhibited by cervical SCT (between €7 and Ti) at 15 minutes, 6 hours and 1 day after anesthesia recovery. We utilized for the GE measurements the method described by Scarpignato et al. (1980). A modification of the method described by Summers et al (1970) was used for the IT measurements and a modification of the method described by Megens et al (1990) for the GIT measurements. We also observed at this point that the inhibition of GE of liquid caused by cervical SCT appears to be the result of motility changes rather than interference of gastric acid secretion changes. In a second phase (protocol 2, N = 121, 160-210 g), we observed that GE and GIT are signiiïcantly inhibited after cervical or thoracic SCT (between €7 and TI or between T4 and 15) throughout the first week after SCT. This demonstrates that the inhibition of GE or GIT did not occur exclusively after r- 19 cervical SCT. For the GE and GIT measurements, we used a modification of the technique described by Reynell & Spray (1956). In the protocol 2, we also performed a bilateral section of the sciatic nerves in five groups of animals (N= 20), named "false paraplegic animals". This group had a pattern of GE /GIT similar to the sham operated group (submitted to laminectomy only),demonstrating that the decrease of physical activity, ^>er se, does not explain the inhibition of GE and GIT after SCT. In the third set of experiments (N = 122, 160-210), called protocol 3, we smdied the neural mechanisms involved in the delay of GE and GIT one day after thoracic SCT. The administration of diazepam or naloxone does not block the phenomenon, demonstrating that the presence of anxiety or opiate mediation do not appear to be the determinant of the GE / GIT inhibition. The intravenous administration of hexamethonium, however, prevented the phenomenon, demonstrating the role of neural, ganglionar pathways. The celiac ganglionectomy and section of the splanchnic nerves also prevented the phenomenon, suggesting the participation ofsympathedc pathways. The iv administration of yohimbine and to a lesser extent of prazosin prevented the development of the phenomenon, suggesting the activation of a receptors. However, the iv administration of propranolol could not prevent the phenomenon, which suggests a possible a receptor specificity, especially if we consider that the bilateral adrenalectomy was also ineffective, showing that the adrenal glands are not involved in the mediation of the phenomenon. However, guanethidine was also unable to block the phenomenon, suggesting that yohimbine and prazosin may act through non adrenergic pathways. 20 The subdiaphragmatic vagotomy also prevented the phenomenon, despite the inefficacy of atropine or L-NAME administration. The vagotomy effect may be explained by a possible direct effect of vagotomy itself on the gastric compliance, modulation of the sympathetic nervous system activity since in rats the vagus nerves carry adrenergic fibers originated at the sympathetic ganglia or finally by the participation ofnoncholinergic vagai pathways. Concerning the hemodynamic changes, the cervical or thoracic SCT caused a decrease in the mean arterial pressure levels which persisted throughout the first three days after SCT. However, mean arterial pressure returned to baseline levels within 7 days after SCT. In contrast, the heart rate persisted decreased imtil 7 days after SCT. In conclusion: 1-Cervical SCT inhibits the GE, IT and GIT of liquid up to 1 day after SCT in awake rats; 2-High SCT (cervical or thoracic) caused a significant inhibition of the GE and GIT of liquid throughout the first week after SCT; 3-The GE / GIT inhibition one day after thoracic SCT appears to be mediated through neural pathways, tto-ough the splanchnic nerves and celiac ganglion, sensitive to subdiaphragmatic vagotomy and administration of hexamethonium, prazosin or yohimbine.